CD146/MCAM distinguishes stem cell subpopulations with distinct migration and regenerative potential in degenerative intervertebral discs. Issue 7 (July 2019) - Wangler, S.; Menzel, U.; Li, Z.; Ma, J.; Hoppe, S.; Benneker, L.M.; Alini, M.; Grad, S.; Peroglio, M.
Summary: Objective: This study aimed to characterize the mesenchymal stem cell (MSC) subpopulation migrating towards a degenerated intervertebral disc (IVD) and to assess its regenerative potential. Design: Based on initial screening for migration towards C-C motif chemokine ligand 5 (CCL5), the migration potential of CD146+ and CD146- mesenchymal stem cells (MSCs) was evaluated in vitro and in a degenerated organ culture model (degeneration by high-frequency loading in a bioreactor). Discogenic differentiation potential of CD146+ and CD146- MSCs was investigated by in vitro pellet culture assay with supplementation of growth and differentiation factor-6 (GDF6). Furthermore, trypsin degenerated IVDs were treated by either homing or injection of CD146+ or CD146- MSCs and glycosaminoglycan synthesis was evaluated by Sulphur 35 incorporation after 35 days of culture. Results: Surface expression of CD146 led to a higher number of migrated MSCs both in vitro and in organ culture. CD146+ and CD146- pellets responded with a similar up-regulation of anabolic markers. A higher production of sulfated glycosaminoglycans (sGAG)/DNA was observed for CD146+ pellets, while in organ cultures, sGAG synthesis rate was higher for IVDs treated with CD146- MSCs by either homing or injection. Conclusions: The CD146+ MSC subpopulation held greater migration potential towards degenerative IVDs, while the CD146- cells induced a stronger regenerative response in the resident IVD cells. These findings were independent of the application route (injection vs migration). From a translational point of view, our data suggests that CD146+ MSCs may be suitable for re-population, while CD146- MSCs may represent the primary choice for stimulation of endogenous IVD cells.